2013
DOI: 10.1016/j.cbi.2013.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anti-inflammatory activity of riparin II (O-methil-N-2-hidroxi-benzoyl tyramine) in animal models

Abstract: Riparin II (RipII), an alkamide isolated from the green fruit of Aniba riparia, was tested in the various animal models of inflammation to investigate its anti-inflammatory activity. Male Wistar rats (180-240g) were treated with RipII by gavage at doses 25 or 50mg/kg, before initiating the inflammatory responses. The tests used were paw edema induced by carrageenan, dextran, histamine or serotonin; peritonitis induced by carrageenan and fMLP, as well as the measurement of MPO activity, TNF-α and Il-1β amount i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 45 publications
0
14
0
1
Order By: Relevance
“…Neutrophil migration to an injury site results in the overproduction of ROS, and leads to oxidative stress and damage of important biomolecules, such as proteins or DNA [36]. Evidence has implicated intracellular ROS production modulating the release of mediators of inflammation [37]. ROS can also regulate adhesion molecule expression on the endothelium, directly influencing the increase of cell recruitment to inflammation sites [37]…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil migration to an injury site results in the overproduction of ROS, and leads to oxidative stress and damage of important biomolecules, such as proteins or DNA [36]. Evidence has implicated intracellular ROS production modulating the release of mediators of inflammation [37]. ROS can also regulate adhesion molecule expression on the endothelium, directly influencing the increase of cell recruitment to inflammation sites [37]…”
Section: Discussionmentioning
confidence: 99%
“…Different species of this family Riparin I, for example, demonstrated antinociceptive activity [8] and antianxiety effects in animal models [9]. Studies with riparin II revealed that it may inhibit directly or indirectly the activity, production or release of pro-inflammatory mediators involved in the generation of pain associated with inflammation [7], and produces significant antidepressant activity [10]. Riparin III, administered intraperitoneally or orally, also showed anxiolytic and antidepressant activity in rodents [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…(7)), for the total concentration protein, [L] free and Συ i can be determined by the linear regression of a plot of [L] T against [M] T (see insert inFig. 5)[41] .…”
mentioning
confidence: 99%
“…Alkaloids derivatives of plants possess potent anti-oxidative and anti-inflammatory properties [6]. It has been described in the literature that several modified or synthetic compounds of substances extracted from Aniba riparia possess several biological effects, which include an anti-nociceptive effect (Riparin I) [7], an anti-inflammatory effect (Riparin II) [8], and an anxiolytic effect (Riparin III) [9]. Some synthetic Riparin-derived compounds (Riparin A, B, C, D, E, and F) also demonstrate an anti-oxidant action in vitro [5].…”
Section: Introductionmentioning
confidence: 99%